2012
DOI: 10.1136/bmjopen-2012-001324
|View full text |Cite
|
Sign up to set email alerts
|

Experiences with global trigger tool reviews in five Danish hospitals: an implementation study

Abstract: ObjectivesTo describe experiences with the implementation of global trigger tool (GTT) reviews in five Danish hospitals and to suggest ways to improve the performance of GTT review teams.DesignRetrospective observational study.SettingThe measurement and monitoring of harms are crucial to campaigns to improve the safety of patients. Increasingly, teams use the GTT to review patient records and measure harms in English and non-English-speaking countries. Meanwhile, it is not clear as to how the method performs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 21 publications
5
37
0
1
Order By: Relevance
“…A recent Danish study showed that the method was initially interpreted differently at different hospitals 25. Small changes in methodology and a gradual development of skills could explain inter-rater disagreement between teams.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Danish study showed that the method was initially interpreted differently at different hospitals 25. Small changes in methodology and a gradual development of skills could explain inter-rater disagreement between teams.…”
Section: Discussionmentioning
confidence: 99%
“…The GTT was used as part of a measurement strategy in both the Health Foundation's Safer Patients Initiative and the 1000 Lives Campaign, 11 and with some success. However, the experience of NHS Wales Hospitals using the IHI GTT was similar to that reported in Danish hospitals, 47 and there was significant variation in rates and experience in its use across hospital sites. As Wales was committed to ongoing harm measurement and monitoring, we set out to compare the methodological approaches in order to identify the optimal approach to quantify the nature and extent of AEs occurring across NHS Wales's acute hospitals over time and ensure the robustness of our current approach.…”
Section: Discussionmentioning
confidence: 83%
“…In a European context, von Plessen et al 47 examined rates of harm using the GTT in five Danish hospitals and reported significant variation between hospitals ranging between 18% and 33%. However, in another, more regulated, smaller study comparing the identification of AEs in 350 orthopaedic admissions in Sweden, the Harvard method detected 155 AEs, compared with 137 events detected by the GTT.…”
Section: A Comparative Analysis Of the Global Trigger Tool And The Hamentioning
confidence: 99%
“…No estudo de Von Plessen et al [14] identificaram diferenças significativas entre taxas de danos encontrados em 5 hospitais, através da ferramenta GTT e taxa média dos EA foi de 25%, dos quais 96% dos danos foram temporários.…”
Section: Resultsunclassified